IDENTIFIKASI KELAYAKAN CHAINSAW PADA KEGIATAN PENEBANGAN UNTUK KESELAMATAN DAN KESEHATAN PEKERJA DI PT. PERAWANG SUKSES PERKASA INDUSTRI (PSPI) - Hutasuhut, Ika Lestari; Sadjati, Emy; Tri Ratnaningsih, Ambar (Fakultas Kehutanan Universitas Lancang Kuning, 2021)
Using chainsaws in logging activities, operators need to ensure that the chainsaws used are fit for use and comply with predetermined standards, particularly in accordance with operational standards that ensure safety and health while working. Modifying the chainsaw is not justified, because it will make the operator unsafe situation. PT. PSPI is one of industrial plantation forest companies in Riau Province which currently produces timber forest products for pulp and paper raw materials. Logging activies in PT. PSPI is still using chainsaw for cutting tree. In logging activities using chainsaws, companies and operators need to ensure that the chainsaws to be used are in proper condition in accordance with predetermined operational standards, the aim to ensure operator stay safety and health while working. The result of this research in identifying chainsaw machines in logging activities carried out at PT. PSPI used 4 indicators, specification of machine chainsaw, the condition of chainsaw, the modification and the age of the chainsaw. Chainsaw is using operators at PT. PSPI is categorized as feasibility enough for use in logging activities with a score of 70.